Superconducting intercalation compounds of metal nitride halides - Fogg, A; Green, V; O'Hare, D (1999)
The crystal structures of the layered host lattices, [β-ZrNBr and [β- HfNCl have been determined. They have been found to be isostructural with rhombohedral SmSI. New lithium intercalation compounds (Li(x)MNX; M = Zr, Hf; X = Cl, Br, I) have been prepared by treatment of either [β-ZrNBr, [β- HfNCl, α-ZrNBr or α-ZrNI with an excess of BuLi in hexane. These intercalates are all superconducting and show transition temperatures (T(c)) of 12, 20, 11 and 11 K respectively. The lithium intercalates of the host lattices β-ZrNBr, α-ZrNBr and α-ZrNI are the first examples of intercalation into these materials.